Application of weighted product method for determining home renovation assistance in Pringsewu district - Muslihudin M.; Ayshwarya B.; Effendi; Yusfika D.; Pribadi M.R.; Susanto F.; Hashim W.; Nguyen P.T.; Maseleno A.; Mukodimah S.; Vellyana D. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
House is a place that is needed by human beside clothing and food. House has important function for all people, a place to unwind and gather with family. A good and comfortable house condition will make family harmony, therefore Pringsewu district government conducts a home renovation assistance program for underprivileged in Pringsewu District. The obstacles faced by local government in implementing home renovation assistance are to determine which citizens are eligible for home renovation assistance. This problem can be overcome by creating an effective and efficient home renovation assistance assessment system. By using the method of weighted product it is expected to help the performance of the local government in Pringsewu District, the method of weighted product was selected because it is able to select alternatives from each alternative. The function of this method is to determine the weight scoew for each alternative and the criteria that have been determined. There are six criteria used in this study, namely: (1) House Wall, (2) Roof Structure (3) Residential Floor (4) Latrine condition (5) Occupation of Head of Household (6) Certificate of House Ownership. In addition the criteria also used criteria weighting score to determine the alternative obtained. The smallest score was in V3 with score of 0.122124 and alternative A3was the alternative selected as the recipient of home renovation assistance in Pringsewu district. BEIESP.